Spontaneous Parametric Down‐Conversion Sources for Multiphoton Experiments. Issue 5 (22nd March 2021) - Zhang, Chao; Huang, Yun‐Feng; Liu, Bi‐Heng; Li, Chuan‐Feng; Guo, Guang‐Can
Abstract: Entangled photon sources are desirable and key elements for photonic quantum information processing. The spontaneous parametric down‐conversion (SPDC) process is a convenient way to produce entangled photon pairs. It has been widely used and has already made great contributions to quantum information science. SPDC sources have been thoroughly studied, and a detailed review, previously lacking, is now appropriate. In this article, different types of SPDC sources suitable for multiphoton experiments are reviewed. A comparison of their respective performances is presented, focusing on the parameters of indistinguishability, collection efficiency, and brightness, from which it is possible to see how the spatial and spectral properties of the SPDC process can be tailored, step by step, to achieve near‐perfect photon pairs. Recent progress on multiplexed heralded single‐photon sources, which effectively mitigate the nondeterministic nature of the SPDC process, is also described. Abstract : Entangled photon pairs are desirable and key resources for photonic quantum information processing. The spontaneous parametric down‐conversion (SPDC) process is a convenient way to produce entangled photon pairs. In this article, different types of SPDC sources suitable for multiphoton experiments are reviewed, and a comparison of their respective performances is presented.